Approved revenue, recurrent and capital estimates. - Nigeria; Nigeria (Lagos : Federal Govt. Press, 1983)
The assessment of the year 1984 and the budget for the 1985 fiscal year.
aia 12/02/2019
Keywords: Budget; Revenue; Öffentlicher Haushalt; Nigeria; Budget; Expenditures, Public; Revenue; Nigeria; Nigeria